Agroecology and Rural Development: An Integrated Approach to Agricultural Sustainability - Pelchor Chicaiza, Jenny Soledad (2025)
The sustainability of agricultural systems in rural areas faces challenges such as climate change, soil degradation, and the growing demand for food. In this context, agroecology has emerged as a strategic alternative to strengthen the resilience of agricultural systems and promote sustainable rural development. This study evaluated its potential through a systematic review of 117 scientific publications and official documents published between 2004 and 2025. The results show that agroecological practices reduce CO₂ emissions, promote biodiversity, regenerate soil quality, and enhance climate resilience, while integrating and revitalizing local knowledge. Moreover, they contribute to improving food security and economic autonomy, with women and young people playing a leading role in transforming their communities. The analysis also identified trends in the state of knowledge, highlighting a conceptual evolution in which agroecology is no longer viewed as a set of isolated practices but rather as an ecosocial paradigm that integrates environmental, social, economic, and political dimensions. This trend reflects a growing academic and institutional recognition of its potential towards fairer and more sustainable agri-food systems.